SUFU haploinsufficiency causes a recognisable neurodevelopmental phenotype at the mild end of the Joubert syndrome spectrum. Issue 9 (21st October 2021) - Serpieri, Valentina; D'Abrusco, Fulvio; Dempsey, Jennifer C; Cheng, Yong-Han Hank; Arrigoni, Filippo; Baker, Janice; Battini, Roberta; Bertini, Enrico Silvio; Borgatti, Renato; Christman, Angela K; Curry, Cynthia; D'Arrigo, Stefano; et al.
Abstract : Background: Joubert syndrome (JS) is a recessively inherited ciliopathy characterised by congenital ocular motor apraxia (COMA), developmental delay (DD), intellectual disability, ataxia, multiorgan involvement, and a unique cerebellar and brainstem malformation. Over 40 JS-associated genes are known with a diagnostic yield of 60%–75%. In 2018, we reported homozygous hypomorphic missense variants of the SUFU gene in two families with mild JS. Recently, heterozygous truncating SUFU variants were identified in families with dominantly inherited COMA, occasionally associated with mild DD and subtle cerebellar anomalies. Methods: We reanalysed next generation sequencing (NGS) data in two cohorts comprising 1097 probands referred for genetic testing of JS genes. Results: Heterozygous truncating and splice-site SUFU variants were detected in 22 patients from 17 families (1.5%) with strong male prevalence (86%), and in 8 asymptomatic parents. Patients presented with COMA, hypotonia, ataxia and mild DD, and only a third manifested intellectual disability of variable severity. Brain MRI showed consistent findings characterised by vermis hypoplasia, superior cerebellar dysplasia and subtle-to-mild abnormalities of the superior cerebellar peduncles. The same pattern was observed in two out of three tested asymptomatic parents. Conclusion: Heterozygous truncating or splice-site SUFU variants cause a novel neurodevelopmental syndrome encompassing COMA and mild JS, which likely represent overlapping entities. Variants can arise de novo or be inherited from a healthy parent, representing the first cause of JS with dominant inheritance and reduced penetrance. Awareness of this condition will increase the diagnostic yield of JS genetic testing, and allow appropriate counselling about prognosis, medical monitoring and recurrence risk.